In situ real-time tracing of hierarchical targeting nanostructures in drug resistant tumors using diffuse fluorescence tomography. Issue 34 (17th July 2019) - Guo, Qianqian; Wang, Yangyun; Zhang, Limin; Zhang, Peng; Yu, Yunjian; Zhang, Yanqi; Li, Chaoxing; Jiang, Shaoyi; Zhang, Xinge
Abstract : Nanoparticles that respond to specific endogenous or exogenous stimuli in tumor tissues are actively being developed to address multidrug resistance owing to multiple advantages, including a prolonged circulation time, enhanced permeability and retention effect, and superior cellular uptake. Abstract : Nanoparticles that respond to specific endogenous or exogenous stimuli in tumor tissues are actively being developed to address multidrug resistance owing to multiple advantages, including a prolonged circulation time, enhanced permeability and retention effect, and superior cellular uptake. Although some exciting results have been obtained, existing nanoparticles have limited routes to overcome the drug resistance of tumor cells; this limitation results in a failure to ablate resistant tumors via intravenous administration. To resolve this dilemma, we developed a smart theranostic nanoplatform with programmable particle size, activatable target ligands and in vivo multimodal imaging. This nanoplatform, which includes stealth zwitterionic coating, was shown to be quickly trapped in tumor tissue from the blood circulation within 5 min. Subsequently, the targeting moieties were activated in response to the acidic tumor microenvironment by triggering the zwitterionic shell detachment, driving the peeled nanoparticles to penetrate into tumor cells. These smart nanoparticles completely inhibited drug-resistant tumor growth and did not cause any damage to normal organ tissues in live animals. The designed nanoplatforms simultaneously acted as a nanoprobe for fluorescence imaging. Moreover, we also used noninvasive pharmacokinetic diffuse fluorescence tomography (DFT) to dynamically monitor and in situ real-time trace the nanoplatforms' behavior throughout the entire tumor in live animals. The nanoplatforms enabled rapid drug accumulation and deep penetration throughout the entire tumor. The rate of drug accumulation after the administration of nanoplatforms was five-fold higher compared with that after the administration of the free drug, which resulted in increased drug delivery efficiency and improved antitumor efficacy. Collectively, this hierarchical vehicle design provides promising insights for the development of theragnosis for multidrug resistant tumors.